الإستراتيجية الإقناعية في سورة الشعراء - خضير, فتيحة; معتوق, مبروكة (University of Eloued جامعة الوادي, 2024)
تسعى هذه الدراسة المسماة " الإستراتيجية الإقناعية" في سورة الشعراء إلى إستخدام الآليات الحجاجية لاقناع المتلقي بالفكر والرأي المقدم، وهناك عدة آيات تستخدم إستراتيجيات اقناعية متنوعة للتأثير على قلوب والعقول وتهدف إلى توجيه الناس نحو الحقيقة والخير وتحث على التذكير والتدبر في آيات الله. وتوصلت الدراسة إلى النتائج والتي منها استخدام القصص والأمثلة التي تعكس عظمة الله وعقابه للظالمين ونجاة المؤمنين، استدعاء العقل والمنطق، وهو الدعوى للتفكير والتدبير في العلامات الكونية والروحانية لهدف اظهار قدرة الله وعظمته، وايضا التأكيد على الرحمة والمغفرة مما يلهم الناس بالتوبة والعودة إلى الله. This study، called the persuasive strategy in Surat Ash-Shu’ara، seeks to use argumentative mechanisms to convince the recipient of the thought or opinion presented. There are several verses that use various persuasive strategies to influence hearts and minds. They aim to direct people towards truth and goodness and encourage remembering and planning in the verses. God. The study reached results، including the use of stories and examples that reflect the greatness of God and His punishment of the oppressors، and the salvation of the believers، invoking reason and logic، which is the call to think and manage the cosmic and spiritual signs، aiming to demonstrate God’s power and greatness، and also emphasizing mercy. Forgiveness inspires people to repent and return to God.
لسانيات عامة
Keywords: الخطاب، الإقناع، الحجاج، الآليات اللغوية، الآليات البلاغية، الآليات الشبه المنطقية.; Discourse - persuasion - arguments - linguistic mechanisms - rhetorical mechanisms - quasi-logical mechanisms - communication